Acts for everyone - Wright, N. T. (Nicholas Thomas) (London : SPCK ; Louisville, Ky. : Westminster John Knox Press, 2008)
N.T. Wright has undertaken a tremendous task: to provide guides to all the books of the New Testament and to include in them his own translation of the entire text. Each short passage is followed by a highly readable discussion, with background information, useful explanations and suggestions, and thoughts as to how the text can be relevant to our lives today. A glossary is included at the back of the book. The series is suitable for group study, personal study, or daily devotions. - From the publisher.
pt. 1. Chapters 1-12 -- pt. 2. Chapters 13-28.
Keywords: Bible. -- Commentaries